Potret Religiusitas Generasi Z Perspektif Maqashid Syariah: Studi Perbandingan Kab. Bintan dan Kota Tanjungpinang - Hudiyani, Zulfa (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Generation Z as a productive age group that grew up amidst technological advances and globalization faces various challenges in maintaining religious values, especially in the Bintan Regency and Tanjungpinang City areas, which are areas with strong cultural and religious backgrounds. This study aims to describe and compare the internalization of Maqashid Syariah values in the religious life of Generation Z in Bintan Regency and Tanjungpinang City, in order to formulate strategic recommendations for improving the development of the religious character of the younger generation in line with the principles of Maqashid Syariah. This study employs a quantitative approach with a comparative method. Primary data were obtained through questionnaires distributed to students at the secondary and tertiary education levels as the unit of analysis. Data collection was conducted via surveys using structured questionnaires, while data analysis involved validity testing, reliability testing, and non-parametric analysis using the Mann-Whitney U Test. The results of the study show that there are differences in the level and form of internalization of Maqashid Syariah values in the religious life of Generation Z in Bintan Regency and Tanjungpinang City, where each region shows excellence in certain aspects of Maqashid Syariah, which reflects the influence of local social, cultural, educational, and religious environmental backgrounds, and is the basis for formulating strategic recommendations for improving the development of the religious character of the younger generation in a contextual and sustainable manner.